Representing Similarity for CBR in XML - Coyle, Lorcan; Doyle, Donal; Cunningham, Padraig (Trinity College Dublin, Department of Computer Science, 2004)
As Case-Based Reasoning has matured as a discipline; the need for a standard means of representing case-based knowledge has come to the fore. While proposals exist for representing the vocabulary and the case-base knowledge containers, there are still no proposed standards for representing similarity or adaptation knowledge. In this paper we present extensions for representing similarity knowledge to CBML, an XML-based CBR language.
Keywords: Computer Science